MEMPELAJARI JALUR DISTRIBUSI PAPRIKA (Capsicum annuum Var. Grossum) SERTA MARGIN PEMASARAN DAN KEUNTUNGANNYA DARI KECAMATAN BATURITI KE KOTA DENPASAR - Ansori, Muhammad; Mulyani, Sri; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 1 (2014): Maret, 2014)
Consumer interest to plant peppers this time began to increase, in line with the need for a clear marketing pattern of distribution is a very useful plant. In Bali, the demand for this crop has increased from year to year. The issue of marketing margin distribution channels and gain peppers from Denpasar to Baturiti unknown. Therefore, this study aimed to determine: (1) the number and types of distribution channels Kecamatan Baturiti peppers from Tabanan regency to the consumers in Denpasar City, (2) the differences between marketing and profit margins on every distribution channel Baturiti peppers from Tabanan to Denpasar City, (3) the differences marketing margins and profits are the highest and lowest of distribution channels peppers. The research method used is qualitative research and the type is survey research with a research instrument is direct interviews.The sampling technique used in this study is purposive sampling, in order to obtain samples as follows: 30% of the sample farmers (14 people), 8 collectors, 4 wholesalers, and retailers 7. There are two results of this study, namely: (1) there are 5 peppers marketing distribution channels through the district of Tabanan Baturiti to Denpasar consumer, (2) the greatest marketing margin distribution channels contained in line-5 that was Rp 22.000,00 (220%) and the smallest marketing margin contained in the distribution line-1 was Rp 6.667,00 (62.50%), the largest profit margins was in line-5 with the amount Rp 20.000,00 (203.24%), the smallest profit margin was on distribution line-1 with the amount Rp 5.856,00 (54.90%). Thus, it can be concluded that the size of the marketing margin in line with the size of the profit margin.
Keywords: 15